1996
DOI: 10.1142/s0218625x96002333
|View full text |Cite
|
Sign up to set email alerts
|

THE SURFACE STRUCTURES OF Pd(100)-(1×1) AND c(2×2)-K

Abstract: The surface structure of the Pd (100)- c (2×2)-K phase formed by adsorption of K at room temperature has been determined by quantitative analysis of low-energy electron-diffraction (LEED) intensity-energy measurements. K atoms occupy four-fold hollow sites on a slightly perturbed substrate. The vertical distance between the K layer and the first Pd layer is determined to be 2.13±0.06 Å, which corresponds to an effective hard-sphere radius of 1.83 Å for the adsorbed K atoms. The second Pd layer is rumpled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…We find that K atoms adsorb preferentially at the hollow site with the K adsorption heights 2.44 Å for p(2 · 2) and 2.50 Å for c ( good agreement with previous experiment [10] and theory [11]. The calculated substrate structure for the c(2 · 2) phase, however, disagrees with the previous LEED structure [10]. We suggest as the origin of this disagreement a possibility of hydrogen contamination of the surface sample used in the LEED study.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…We find that K atoms adsorb preferentially at the hollow site with the K adsorption heights 2.44 Å for p(2 · 2) and 2.50 Å for c ( good agreement with previous experiment [10] and theory [11]. The calculated substrate structure for the c(2 · 2) phase, however, disagrees with the previous LEED structure [10]. We suggest as the origin of this disagreement a possibility of hydrogen contamination of the surface sample used in the LEED study.…”
Section: Introductionsupporting
confidence: 91%
“…The LEED result of a larger d 12 for K/Pd(1 0 0) reminds us of a previous dispute about Dd 12 of the clean Pd(1 0 0) surface: While DFT studies [18][19][20] predicted top-layer contractions of Dd 12 $ À 1%, LEED studies [10,21,22] reported relatively large expansions of Dd 12 = 2.5-4.6%.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations